Woman, gender and colonialism : debates on the ideal womanhood in Korean Society c. 1910-1945 - Ngm, Vivian Hui Ting (Nanyang Technological University, 2020)
The debate on the woman question in Korea can be observed to have its beginnings when Korea was under Japanese colonial rule. During this time, the debates surrounding the woman question focused on defining the new ideal womanhood for Korean women. Koreans were facing the constant dilemma and struggle arising from trying to protect Korea’s identity and resist the Japanese colonial rule. Due to the influence of neo-Confucianism, the role and status of women was part of Korea’s society and culture. As such, it is interesting to examine the process of this debate and discussion to change this ideal. In this paper, I argue that the combination of the prescribed gender roles of Confucian-influenced Korean culture, the “colonized” status of Korea under Japan and the extensive assimilation policies that threatened to take away the Korean identity has pitted Korean men against women in the negotiation of the Korean womanhood during the colonial period. While the notion of femininity of Korean women has changed during the colonial period, emphasis of women’s role as distinct from men persisted despite the changes and thus, the discrimination of women was still prevalent by the end of the 1940s.